Digitalisation and Modernity of Capital Stock in Europe - Heike Belitz; Martin Gornig (Intereconomics, 2023)
Digitalisation has become one of the core concepts in European modernisation. Whileinvestment in computer hardware, telecommunications equipment, software and databaseshas increased over the years, the degree of modernity of the overall capital stock has not.This paper examines whether there is a relationship between digitalisation and the changesin the degree of modernity of capital stock in different sectors in 13 European countries. Ouranalysis shows that a higher degree of digitalisation leads to a more modern capital stock.That being said, comprehensive modernisation of capital stock will take more than an increasein the degree of digitalisation. Selective investment subsidies for digital assets, such as thoseprovided at the EU level and in individual member states, are not enough. What Europe needsis for investment activity to be promoted across the board.
Keywords: E22; L16; O33; 330; capital stock; digitalization; EU states; Kapitalstock; Digitalisierung; EU-Staaten